An Incipient Mutiny : The Story of the U.S. Army Signal Corps Pilot Revolt - Messimer, Dwight R., 1937- (Book collections on Project MUSE., 2020)
""An Incipient Mutiny" traces the creation of the U.S. Army Signal Corps Aeronautical Division in 1907 up to the establishment of the Air Service of the National Army in 1918. It is a shocking account of shortsightedness, mismanagement, criminal fraud, and cover-up that led ultimately to a pilot revolt against the military establishment. Dwight R. Messimer focuses on the personalities of the pilots who initiated the rebellion and on the Signal Corps officers whose mismanagement brought it on."